The changing role of European documentation centres and how 'Brexit' might affect the network - Watson, M (Cambridge University Press, 2017)
European Documentation Centres (EDCs) are neutral collections of official publications of the European Union, open to the public and normally housed in academic institutions throughout the European Union (EU). EDC status entitles the host organisation to receive one copy of the most significant publications and documents of the EU. The EDC network goes back to 1963, and its primary purpose has always been the support of academic research into European integration. The decision to trigger Article 50 of the Treaty on European Union clearly raises questions about role of the EDCs in the United Kingdom after ‘Brexit’.